Optimizing recombinant mini proinsulin production via response surface method and microbioreactor screening - Esra Ayan; Ali Özhan Aytekin; Ahmet Kati; Hasan Demirci (PLoS ONE, 2025)
The increasing demand for efficient recombinant insulin production necessitates the development of scalable, high-yield, and cost-effective bioprocesses. In this study, we engineered a novel mini-proinsulin (nMPI) with enhanced expression properties by shortening the C-peptide and incorporating specific residue substitutions to eliminate the need for enzymatic cleavage. To optimize its production, we applied a hybrid approach combining microscale high-throughput cultivation using the BioLector microbioreactor and statistical modeling via response surface methodology (RSM). Critical medium components were first screened using Plackett–Burman Design (PBD) and refined through Central Composite Design (CDD), identifying glycerol as the most influential factor for yield. Among the four statistically derived formulations, Scenario III demonstrated the highest productivity in the microscale platform (13.00 g/L) and maintained strong performance upon scale-up to a 3-L bioreactor (11.5 g/L). The optimized medium balanced carbon and nitrogen sources to enhance cell viability and maximize protein expression. This study not only confirms the predictive accuracy and scalability of the hybrid optimization system but also introduces a robust production platform for nMPI that can be translated into industrial settings. The workflow presented here can serve as a model for the development of efficient expression systems for complex recombinant proteins in E. coli.